Service Quality, Satisfaction and Trust: a Study of Public Hospitals in Bandung, Indonesia - Susan, Marcellia; ., . (International Journal of Engineering and Technology, 2018)
Research on service quality has been performed by researchers on various research objects. In many previous studies, service quality provided by service providers became the factor that affects customer satisfaction and other various research variables. The study was conducted at public hospitals that offer healthcare services with a focus on service quality. The purpose of this study was to analyze the service quality provided by public hospitals, and to test their effect on the satisfaction and trust of patients or attendants. The objects of this research are the public hospitals in Bandung with the patients or attendants as the unit of analysis. Primary data were obtained through the dissemination of questionnaires on patients or attendants to obtain data on their evaluation of service quality of public hospitals, and their satisfaction and trust towards public hospitals. Obtained data was processed using structural equation modeling to confirm causality of related research variable. The results depict the service quality provided by public hospitals in Bandung covering infrastructure, personnel quality, clinical care process, administrative procedures, safety indicators, and social responsibility. Moreover, the results of hypothesis testing show that service quality has an influence on patient satisfaction, and ultimately affects their trust in the hospital.Â Â